Overcoming 'Anti-Vaccination Scepticism': Seeking a Solution to the Situation - Tatiana A. Kaliuzhnaia; Marina V. Fedoseenko; Leyla S. Namazova-Baranova; Anna G. Gaivoronskaya; Firuza Ch. Shakhtakhtinskaya; Natalia E. Tkachenko; Marika I. Broeva; Tatiana E. Privalova; Elena A. Vishneva; Dariya S. Chemakina; Yuliya Yu. Kasatkina; Ksenia М. Gaivoronskaya (Union of pediatricians of Russia, 2018)
Background. The problem of distrust of immunization is widespread not only in Russia but also all over the world. Many parents refuse to vaccinate their child reasoning that the vaccines can harm their health, the immune system may not cope with the body burden; and some doctors themselves discourage parents from vaccination. Our aim was to assess the attitude of doctors and parents towards vaccination whose children are vaccinated completely or partially; to study the most frequent reasons for refusals of vaccination by parents. Methods. We used the questionnaires for parents (n = 114) who brought their children for vaccination for the first time or repeatedly; and the questionnaires for students of 4-6 courses and interns of medical universities (n = 336) who expressed their sentiments towards vaccination and demonstrated the knowledge of the national and regional immunization schedules. AstonGroup also conducted studies among physicians of different specialties (n = 307) on the most frequent reasons for refusals of vaccination. Results. In most cases, the parents' attitude towards vaccination was positive. One in three patient representatives considered that he was fully acquainted with immunization issues, and more than half wanted to be vaccinated only within the national immunization schedule. In almost 100% of cases, parents had trust in information about vaccination received from a doctor. The results of the AstonGroup survey showed that the most frequent medical exemptions were given by neurologists, immunologists, and surgeons. And the parents themselves, who brought their children to see doctors, reasoned their refusals of vaccination with fear of complications and also considered vaccination to be harmful and useless. The doctors participating in the survey offered methods for influencing the parents, namely: providing them with accessible information about vaccinations included in the national immunization schedule as well as about the experience of using vaccines, including other countries. Discussion. The survey revealed insufficient knowledge of the national immunization schedule among students as well as cautious attitude towards vaccination issues and the trust in vaccination myths among legally authorized representatives of patients. Conclusion. The effective measures to combat 'anti-vaccination scepticism' are lectures for parents; personal, social and health education at pediatric sites as well as continuing medical education.